2013
DOI: 10.1371/journal.pone.0071737
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Alters Host Genotype-Specific Susceptibility to Chytrid Infection

Abstract: The cost of parasitism often depends on environmental conditions and host identity. Therefore, variation in the biotic and abiotic environment can have repercussions on both, species-level host-parasite interaction patterns but also on host genotype-specific susceptibility to disease. We exposed seven genetically different but concurrent strains of the diatom Asterionella formosa to one genotype of its naturally co-occurring chytrid parasite Zygorhizidium planktonicum across five environmentally relevant tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 42 publications
4
64
0
Order By: Relevance
“…Field studies have shown that relatively cold winters inhibit the activity of chytrids and thereby provide the host with an opportunity to bloom. In contrast, warm winters seem to facilitate chytrids, preventing the host to form a bloom (Van Donk & Ringelberg, ; Ibelings et al ., ; Gsell et al ., ). Furthermore, laboratory experiments showed enhanced chytrid infections with increasing temperature over a range of 1–16 °C, but infection was inhibited at a temperature of 21 °C (Gsell et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Field studies have shown that relatively cold winters inhibit the activity of chytrids and thereby provide the host with an opportunity to bloom. In contrast, warm winters seem to facilitate chytrids, preventing the host to form a bloom (Van Donk & Ringelberg, ; Ibelings et al ., ; Gsell et al ., ). Furthermore, laboratory experiments showed enhanced chytrid infections with increasing temperature over a range of 1–16 °C, but infection was inhibited at a temperature of 21 °C (Gsell et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, warm winters seem to facilitate chytrids, preventing the host to form a bloom (Van Donk & Ringelberg, ; Ibelings et al ., ; Gsell et al ., ). Furthermore, laboratory experiments showed enhanced chytrid infections with increasing temperature over a range of 1–16 °C, but infection was inhibited at a temperature of 21 °C (Gsell et al ., ). Not only transmission rates and virulence of parasites are important, but also chytrid physiological characteristics that are affected by temperature can be important for its success.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is potentially mediated by the effects of temperature variability on pathogen emergence, development time, or transmission dynamics (Hernandez, Poole, & Cattadori, ; Karvonen, Rintamaki, Jokela, & Valtonen, ; Lafferty, ; Macnab & Barber, ; Paull & Johnson, ; Studer & Poulin, ), or differences in thermal tolerance ranges of host and pathogen species (Altizer et al., ; Lafferty & Kuris, ). If the thermal tolerance range of the host is broader than that of the pathogen, extreme hot or cold temperatures may provide a thermal refuge, where pathogen pressure is not as high (Gsell, de Senerpont Domis, Van Donk, & Ibelings, ; Marinkelle & Rodriguez, ; Schoebel, Tellenbach, Spaak, & Wolinska, ). Thermal variability may influence host behavior, feeding ecology, and survival of both host and pathogen species (Lafferty & Kuris, ), the net effect of which determines the resulting relationship between temperature variability and infection dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…shorter development time results in reduced zoospore production) and a reduction in the infective zoospore lifetime (Bruning & Ringelberg, ; Bruning, ,b). With the exception of 2010, peaks in I p occurred during late spring when temperatures were near the optimum for chytrid growth (16 °C; Gsell et al ., ). Summer temperatures exceeded this optimum window, possibly accounting for the decreased abundance of sporangia associated with diatom hosts.…”
Section: Discussionmentioning
confidence: 99%